Fifty years of the international court of justice essays in honour of Sir Robert Jennings - Lowe, Vaughan; Fitzmaurice, Malgosia (Cambridge University Press, 2009)
This multi-author text offers a critical review of the work of the International Court of Justice, and its relations with the political organs of the United Nations, during the past fifty years. Its purpose is to draw together the reflections of the most eminent international judges, practitioners and academics in the field of public international law, on the way that the Court has handled the matters put before it. No other text has such a distinguished team of specialist contributors, or the comprehensive coverage of this volume.